2004
DOI: 10.1111/j.1440-1843.2004.00600.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological study of bronchogenic carcinoma

Abstract: Bidi smoking is an important contributory factor in the development of bronchogenic carcinoma in India, and approximately 25% of patients with bronchogenic carcinoma are non-smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
27
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 9 publications
(13 reference statements)
10
27
4
Order By: Relevance
“…Hence the importance of tobacco cessation programmes in the community as well as mass education and awareness programme among adolescents should be strongly implemented. The proportion of lung cancer incidence among non-smokers is approximately 20%, which correlates with other studies conducted in India (Rajasekaran et al, 1993;Gupta et al, 1998;Prasad et al, 2004).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Hence the importance of tobacco cessation programmes in the community as well as mass education and awareness programme among adolescents should be strongly implemented. The proportion of lung cancer incidence among non-smokers is approximately 20%, which correlates with other studies conducted in India (Rajasekaran et al, 1993;Gupta et al, 1998;Prasad et al, 2004).…”
Section: Discussionsupporting
confidence: 86%
“…The present study showed inconsistent results on the distribution of histologic type of cancer compared with the other studies conducted within India (Gupta et al, 1998;Thippanna et al, 1999;Khan et al, 2006;Prasad et al, 2009;Singh et al, 2010). However several studies have pointed out that majority of the lung cancer cases were diagnosed in the advanced stages of the disease (Thippanna et al, 1999;Prasad et al, 2004;Mohan et al, 2007).…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…6 Another study by Prasad R et al reported the mean age to be 57 years. 7 The male to female ratio was 2.4: 1. The ratio was lower compared to the other Indian studies where the male to female ratio varied from 4.5:1 to 7.8:1.…”
Section: Discussionmentioning
confidence: 96%